Understanding the Anatomy of Posterior Cervical Interfascial Space: Implications for Regional Blocks and Pain Management. A Narrative Review - Yufeng Zhang; Huili Li; Songchao Xu; Ruijuan Guo; Danxu Ma; Yun Wang (Pain and Therapy)
Abstract The posterior cervical area exhibits a complex anatomy comprising fascia, nerves, and muscles. With the widespread adoption of ultrasound in regional anesthesia, numerous posterior cervical interfascial plane block techniques have been developed in recent years. The injectate spreads along the fascial plane, blocking nerves that traverse the interfascial space after being injected into the target plane. The posterior cervical interfascial blocks have been manifesting the great potential for perioperative analgesia and chronic pain management in the head, neck, and shoulder regions. However, a comprehensive review of these methods as well as their indications, contraindications, and complications remain lacking. This article summarizes the anatomy of the posterior cervical musculofascial layers, highlighting the characteristics of interfascial plane block techniques and their potential limitations. By using the fascial anatomy as an entry point for studying interfascial plane blocks, it enhances our understanding of the mechanisms underlying the efficacy and complications of these block techniques. It not only reviews well-studied blocks such as trapezius plane (TP), multifidus cervicis plane (MCP), inter-semispinal plane (ISP), and erector spinae plane (ESP) block but also includes recently developed techniques from the past 5 years, such as the retrolaminar cervical block, serratus posterior superior intercostal plane (SPSIP) block, and C2 dorsal root ganglion (DRG) “three-in-one” block. The available evidence suggests that while posterior cervical interfascial plane blocks effectively target the dorsal rami of cervical nerves, non-posterior cervical block techniques also exhibit analgesic potential for the posterior cervical region. This review aims to provide insights for further exploration of novel approaches in this emerging field. In conclusion, posterior cervical interfascial plane blocks demonstrate significant clinical value and warrant further development and optimization.